Calprotectin: from biomarker to biological function. Issue 10 (18th June 2021) - Jukic, Almina; Bakiri, Latifa; Wagner, Erwin F.; Tilg, Herbert; Adolph, Timon E.
Abstract : The incidence of inflammatory bowel diseases (IBD) emerged with Westernisation of dietary habits worldwide. Crohn's disease and ulcerative colitis are chronic debilitating conditions that afflict individuals with substantial morbidity and challenge healthcare systems across the globe. Since identification and characterisation of calprotectin (CP) in the 1980s, faecal CP emerged as significantly validated, non-invasive biomarker that allows evaluation of gut inflammation. Faecal CP discriminates between inflammatory and non-inflammatory diseases of the gut and portraits the disease course of human IBD. Recent studies revealed insights into biological functions of the CP subunits S100A8 and S100A9 during orchestration of an inflammatory response at mucosal surfaces across organ systems. In this review, we summarise longitudinal evidence for the evolution of CP from biomarker to rheostat of mucosal inflammation and suggest an algorithm for the interpretation of faecal CP in daily clinical practice. We propose that mechanistic insights into the biological function of CP in the gut and beyond may facilitate interpretation of current assays and guide patient-tailored medical therapy in IBD, a concept warranting controlled clinical trials.